2007
DOI: 10.1002/jcp.21110
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chondrocyte differentiation by the actin cytoskeleton and adhesive interactions

Abstract: Chondrocyte differentiation is a multi-step process characterized by successive changes in cell morphology and gene expression. In addition to tight regulation by numerous soluble factors, these processes are controlled by adhesive events. During the early phase of the chondrocyte life cycle, cell-cell adhesion through molecules such as N-cadherin and neural cell adhesion molecule (N-CAM) is required for differentiation of mesenchymal precursor cells to chondrocytes. At later stages, for example in growth plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
176
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(195 citation statements)
references
References 143 publications
(135 reference statements)
11
176
0
2
Order By: Relevance
“…Beier et al reported that RhoA/Rock signaling suppresses chondrogenesis through the control of Sox9 expression and actin organization (33). Rho-ROCK signal transduction is involved in inhibition of chondrocyte differentiation as well as modulation of chondrocyte metabolism (34). Our data showing enhancement of proteoglycan staining in ATDC5 cells treated with AS1892802 supports their results.…”
Section: Discussionsupporting
confidence: 89%
“…Beier et al reported that RhoA/Rock signaling suppresses chondrogenesis through the control of Sox9 expression and actin organization (33). Rho-ROCK signal transduction is involved in inhibition of chondrocyte differentiation as well as modulation of chondrocyte metabolism (34). Our data showing enhancement of proteoglycan staining in ATDC5 cells treated with AS1892802 supports their results.…”
Section: Discussionsupporting
confidence: 89%
“…Studies by our group and others have shown that Rho GTPases are important regulators of chondrocyte proliferation and differentiation (Kerr et al, 2008;Kumar and Lassar, 2009;Wang and Beier, 2005;Wang et al, 2004;Woods and Beier, 2006;Woods et al, 2009b;Woods et al, 2005;Woods et al, 2007a;Woods et al, 2007b). Rho family GTPases act as molecular switches that become activated in response to specific extracellular stimuli, including growth factors and integrin ligands, through the activity of guanine nucleotide exchange factors that exchange GTP for GDP (Heasman and Ridley, 2008;Vega and Ridley, 2007;Vega and Ridley, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Activated, GTPbound Rho proteins then interact with a large variety of downstream effectors, including cytoskeletal regulators and various kinases, to control a number of cellular events such as cell migration, cell cycle progression and gene expression. During the early steps of chondrogenesis, regulation of actin dynamics and cellular morphology appear to mediate many of the effects of Rho GTPases (Beier and Loeser, 2010;Woods and Beier, 2006;Woods et al, 2005;Woods et al, 2007a). However, additional mediators are probably involved in these activities of Rho GTPAses, in particular after cells have differentiated into chondrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the transcription of truncated isoform may be related to rearrangement of the actin cytoskeleton and subsequent morphological changes as observed in glial cells (Ohira et al, 2006(Ohira et al, , 2007 through a BDNF-independent pathway. In fact, it is known that Rho GTPases are of particular interest in chondrocytes because of their role in connecting signals from the extracellular matrix to the actin cytoskeleton and cellular morphology, which in turn can control cellular activities, such as cell cycle progression and gene expression (Woods et al, 2007).…”
Section: Discussionmentioning
confidence: 99%